2022
DOI: 10.32598/rj.23.2.3305.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adlerian Play Therapy on Working Memory of Female Students Seven to Twelve Years Old With Mild Intellectual Disability

Abstract: Objective Intellectual disability is a common neurodevelopmental disorder. Working memory deficit can affect children. One of the effective methods in the field of learning is playing games and the application of play therapy techniques. In this method, children are allowed to practice useful social behaviors and experience new thoughts and feelings in a safe environment with supportive relationships. This study aimed to examine the effectiveness of Adlerian play therapy on the working memory of female student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Mirzaie et al (2019) used individual AdPT with children and adolescents (6-15 years old) diagnosed with attention deficit/hyperactivity disorder and two comparative groups (i.e., filial therapy and no treatment control). Two more randomized control trials were also identified (Bilqis, 2021;Johari et al, 2022) but will not be included due to additional adaptations, which clearinghouses note are deviations from the original model outlined in the AdPT treatment manual and must be evaluated separately. Clearinghouses may also miss dissertation studies that show promising results, such as Dickinson (2019) and Akay (2013).…”
Section: Adptmentioning
confidence: 99%
“…Mirzaie et al (2019) used individual AdPT with children and adolescents (6-15 years old) diagnosed with attention deficit/hyperactivity disorder and two comparative groups (i.e., filial therapy and no treatment control). Two more randomized control trials were also identified (Bilqis, 2021;Johari et al, 2022) but will not be included due to additional adaptations, which clearinghouses note are deviations from the original model outlined in the AdPT treatment manual and must be evaluated separately. Clearinghouses may also miss dissertation studies that show promising results, such as Dickinson (2019) and Akay (2013).…”
Section: Adptmentioning
confidence: 99%
“…Attention is one of the cognitive functions that can benefit from cognitive rehabilitation. Attention is a complex mental operation that includes focusing or engaging to hold or endure and listening to the bell for an extended period, decoding the features of the stimulus, and shifting concentration from one aim to another [5]. Identifying attention components is difficult for a variety of reasons.…”
Section: Introductionmentioning
confidence: 99%